Penguatan Literasi Digital Guru dan Siswa Sanggar Bimbingan Kampung Baru dan Kepong melalui Pembelajaran Holistik Berdiferensiasi Konten Digital - Andriyani, Andriyani; Djannah, Sitti Nur; Akmal, Akmal; Aprilia, Dede Dwi; Muhajir, Moch (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The changing role of teachers as creative and innovative facilitators in solving problems in learning is a challenge for teachers who don't yet have good digital skills. Moreover, it is a challenging problem for the teachers who must dedicate to educate students in non-formal educational institutions that have limited digital learning facilities that support learning, such as the Tutoring Studio in Kuala Lumpur, Malaysia. Students' conditions are very diverse with complex socio-cultural problems. This has implications for the lack of technology integration in learning. Therefore, the aim of the community service activities carried out at the Kampung Baru and Kepong Tutoring Studio is to strengthen the digital literacy of teachers and students through the use of technology in content-differentiated holistic learning. The methods for implementing service activities consist of measuring teacher competency and student abilities, socialization of learning technology, training in the preparation and digitization of electronic learning devices, content-based holistic learning with digital teacher teaching materials, as well as evaluation regarding the impact of activities on the digital literacy abilities of teachers and students. The evaluation results show that there has been an increase in the digital literacy skills of teachers and students after implementing the results of teacher training in student learning. Teachers' ability to apply their functional skills to digital devices can be seen in the preparation of several learning tools such as simple worksheets. Likewise, students already have good technical skills in accessing, understanding, and using information from various digital sources. Beside that, students can also choose important and more critical information when using their smartphones to support their learning process because the teacher's digital teaching materials are presented in a more interesting way.